An observational study of physical, cognitive and social activities in rehabilitation inpatients. (25th February 2020) - McRae, Prue; Bew, Paul; Smith, Simon; Mudge, Alison
Abstract: Objectives: To describe patient behaviour related to mobility in a rehabilitation inpatient setting and compare intensive and Transition Care Program (TCP, slow‐stream rehabilitation) models. Methods: Prospective cross‐sectional design including weekday and weekend sampling in two rehabilitation wards (one intensive and one TCP) in a publicly funded facility. A single trained observer undertook behavioural mapping, observing patient location, mobility, activity and company on all inpatients 8 am ‐4 pm using a structured 2‐minute observation protocol. Observations were summarised and compared between wards. Results: We observed 74 inpatients on a Tuesday and 77 on a Sunday. Participants spent 7% (median) of daytime standing or walking. They spent 62%‐87% in their room, 22%‐40% sleeping or resting and 74%‐86% alone. The only significant difference between wards was time spent off ward on Tuesday. Activity was lower on Sunday. Conclusions: Time spent in physical, cognitive and social activities is low in inpatient rehabilitation and TCP wards.